NEGATIVE CORRELATION BETWEEN LEUKOCYTE COUNT AND HIGH DENSITY LIPOPROTEIN IN TYPE 2 DIABETES MELLITUS PATIENTS IN SANGLAH GENERAL HOSPITAL, BALI - Ratnasari, Ni Luh Made Novi; Saraswati, Made Ratna; Losen Adnyana, I Wayan; Sudhana, I Wayan (Bali Journal of Medical and Health Sciences; vol 1,no 2(2017):volume 1 no 2 Mei 2017)
Type 2 diabetes mellitus (T2DM) is group with high cardiovascular disease (CVD) risk. Inflammation which is reflected by increasing leukocyte number, CRP, and lipid profile. Despite that, infection as one of diabetic complication commonly occurs in patient with T2DM. The dyslipidemia status reflected by lipid profile composition. So here, we aim to evaluate the relationship between leukocyte count with lipid profile to know the association between traditional and non-traditional risk factor of CVD in T2DM patient. The type of this research is cross sectional analytic research with 94 samples was enrolled into this study. The data is obtained initially by collecting from the quistionare and from laboratorium examination. Mean of samples’ age is 55 years and large number of patients had leukocytosis as reflected by high value of its mean (15.02±8.78 x 10 3 /?L). We found that 56.4% of the subjects fall into worst category of glycemic control (Hb A1C ). Only 24.5% of the subjects had good glycemic control. Further evaluation showed that there were significant strong negative correlations between leukocyte count with HDL (r= -0.555; p=0.000). Inflammation which mainly related to infectious disease is common among T2DM patients which increase CVD risk by lowering HDL and worsening glycemic control. Keywords: Type 2 Diabetes Mellitus, lipid profile, leukocyte count